Antibacterial Activity of Endophytic Fungi from Sembukan (Paederia foetida L.) Leaves - Hary Widjajanti; Christina Vivid Handayani; Elisa Nurnawati (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
The antibiotic resistance of phatogenic bacteria has become a serious health problem and has encouraged the search for novel and effective antimicrobial metabolites. Meanwhile, endophytic fungi have great potential as a natural source for antimicrobial agents. The endophytic fungi that live in plant tissue produces secondary metabolites which potentially act as an antibacterial compound. The isolation of fungi for antibacterial sources reduces the large amount of plant as a source of antibacterial agents. Hence, this study aims to obtain endophytic fungi isolates from Paederia foetida L. that are capable of producing secondary metabolites as antibacterial, carry out in vitro tests to verify the antibacterial properties of secondary metabolites of the Paederia foetida L. endophytic fungi, and identify the potential of Paederia foetida L. endophytic fungi in producing antibacterial compounds. The antibacterial activity was tested against Escherichia coli ATCC8739 and Staphylococcus aureus ATCC6538 while seven isolates of endophytic fungi that potentially produced antibacterial were obtained from Sembukan (P. foetida L.). The results showed that antibacterial activities of SL1, SL4 and SL6 secondary metabolites against S. aureus ATCC6538 and E. coli ATCC8739 were moderate to strong activities. Furthermore, the Minimum Inhibition Concentration (MIC) of secondary metabolites extract of SL1 against S. aureus ATCC6538 value was 250 ????g/mL while the values of MIC extract of SL4 against S. aureus ATCC6538 and E. coli ATCC8739 were 125 ????g/mL and 250 ????g/mL respectively and MIC extract of SL6 against E. coli ATCC8739 value was 125 ????g/mL. The secondary metabolites extract of SL1 isolate were alkaloid and tannin, SL4 were phenolic and alkaloid while SL6 isolate were alkaloid and terpenoid. Hence, endophytic fungi SL1 isolate was identified as Fusarium sp., SL4 as Dematophora sp., and SL6 isolate as Acremonium sp.